Oxidative Stress and Its Implications in the Right Ventricular Remodeling Secondary to Pulmonary Hypertension - Mikhael, Matthew; Makar, Christian; Wissa, Amir; Le, Trixie; Eghbali, Mansoureh; Umar, Soban (Frontiers in Physiology, 2019)
Pulmonary hypertension (PH) is a pulmonary vascular disease characterized by increased pulmonary artery pressures. Long standing pulmonary arterial pressure overload leads to right ventricular (RV) hypertrophy, RV failure and death. RV failure is a major determinant of survival in PH. Oxidative stress has been associated with the development of RV failure secondary to PH. Here we summarize the structural and functional changes in the RV in response to sustained pulmonary arterial pressure overload. Furthermore, we review the pre-clinical and clinical studies highlighting the association of oxidative stress with pulmonary vasculature and RV remodeling in chronic PH. Targeting oxidative stress promises to be an effective therapeutic strategy for the treatment of RV failure.